Quality Management in South Africa - Kwanten, Tine (2012)
ABSTRACT This dissertation addresses something which is extremely important for both individual enterprises as well as entire nations i.e. the ability to deliver quality goods and services. Notwithstanding its geographical distant location, South Africa is increasingly becoming a more important participant in the global economy and increasingly relying on export. Local businesses therefore need to meet international quality standards. For this matter this dissertation investigated the state of quality management in the country, and constitutes a temperature-check of current practices. The research conducted was quantitative in nature and primary data was collected by means of an online survey. A total of 129 individuals completed the survey, of which 111 were perceived useful. The results of the study showed that the use of the different tools and initiatives this study was generally in line with previous research (Dedhia, 2000). The majority of respondents have adopted the ISO 9000 series whereas TQM and Six Sigma are used on a more limited basis and Quality Function Deployment and Design of Experiments are only used by a very limited amount of respondents. The use of nearly all tools and techniques is expected to rise in popularity in the future. The main reason cited for using quality tools and techniques were customer requirements and respondents indicated that they benefit the most from their quality efforts by an increase in customer satisfaction. The findings indicate that leaders encourage employee empowerment and acknowledge of individual contributions to quality. A large proportion of respondents agreed that everyone is responsive for quality. This study detected regional differences between Gauteng and the Western Cape, albeit solely for a small part of the quality dimensions included in the survey. Statistical analyses showed that the use of quality tools and techniques is related to company size and export level. The findings can be of particular use to management of multinationals in designing their global QM practices. They will benefit from an awareness of both the differences and similarities witnessed in South Africa. Moreover, this dissertation also pointed out that insufficient resources are the main obstacle to respondents’ quality efforts. If the South African government wants to increase the overall competiveness of the country, it needs to address the limitations that SMMEs have, in terms of providing the necessary incentives, but also in terms of training and knowledge sharing.